Deficiency of the RNA-binding protein ELAVL1/HuR leads to the failure of endogenous and exogenous neuroprotection of retinal ganglion cells - Pacwa, Anna; Machowicz, Joanna; Akhtar, Saeed; Rodak, Piotr; Liu, Xiaonan; Pietrucha-Dutczak, Marita; Lewin-Kowalik, Joanna; Amadio, Marialaura; Smedowski, Adrian (Frontiers in Cellular Neuroscience, 2023)
Introduction ELAVL1/HuR is a keystone regulator of gene expression at the posttranscriptional level, including stress response and homeostasis maintenance. The aim of this study was to evaluate the impact of hur silencing on the age-related degeneration of retinal ganglion cells (RGC), which potentially describes the efficiency of endogenous neuroprotection mechanisms, as well as to assess the exogenous neuroprotection capacity of hur-silenced RGC in the rat glaucoma model. Methods The study consisted of in vitro and in vivo approaches. In vitro, we used rat B-35 cells to investigate, whether AAV-shRNA-HuR delivery affects survival and oxidative stress markers under temperature and excitotoxic insults. In vivo approach consisted of two different settings. In first one, 35 eight-week-old rats received intravitreal injection of AAV-shRNA-HuR or AAV-shRNA scramble control. Animals underwent electroretinography tests and were sacrificed 2, 4 or 6 months after injection. Retinas and optic nerves were collected and processed for immunostainings, electron microscopy and stereology. For the second approach, animals received similar gene constructs. To induce chronic glaucoma, 8 weeks after AAV injection, unilateral episcleral vein cauterization was performed. Animals from each group received intravitreal injection of metallothionein II. Animals underwent electroretinography tests and were sacrificed 8 weeks later. Retinas and optic nerves were collected and processed for immunostainings, electron microscopy and stereology. Results Silencing of hur induced apoptosis and increased oxidative stress markers in B-35 cells. Additionally, shRNA treatment impaired the cellular stress response to temperature and excitotoxic insults. In vivo, RGC count was decreased by 39% in shRNA-HuR group 6 months after injection, when compared to shRNA scramble control group. In neuroprotection study, the average loss of RGCs was 35% in animals with glaucoma treated with metallothionein and shRNA-HuR and 11.4% in animals with glaucoma treated with metallothionein and the scramble control shRNA. An alteration in HuR cellular content resulted in diminished photopic negative responses in the electroretinogram. Conclusions Based on our findings, we conclude that HuR is essential for the survival and efficient neuroprotection of RGC and that the induced alteration in HuR content accelerates both the age-related and glaucoma-induced decline in RGC number and function, further confirming HuR’s key role in maintaining cell homeostasis and its possible involvement in the pathogenesis of glaucoma.